2014
DOI: 10.1167/iovs.14-13933
|View full text |Cite
|
Sign up to set email alerts
|

The Demethylating Agent 5-Aza Reduces the Growth, Invasiveness, and Clonogenicity of Uveal and Cutaneous Melanoma

Abstract: Citation: Rajaii F, Asnaghi L, Enke R, Merbs SL, Handa JT, Eberhart CG. The demethylating agent 5-Aza reduces the growth, invasiveness, and clonogenicity of uveal and cutaneous melanoma. Invest Ophthalmol Vis Sci. 2014;55:6178-6186. DOI:10.1167/ iovs.14-13933 PURPOSE. Uveal melanoma is the most common primary intraocular malignancy in adults. Although local disease can be controlled with radiation therapy or enucleation, many cases are complicated by metastases, which account for the significant mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…While large-scale epigenetic changes have been documented in UM tumors, and these changes have been significantly related to prognosis, there are currently no approved treatments using these agents in UM. In vitro, treatment with epigenetic modifying drugs has been shown to reduce growth and invasiveness in UM cell lines, and decitabine (a DNMT inhibitor) in combination with MEK inhibition has been shown to suppress growth in UM cells [ 39 , 40 ]. Additionally, decitabine has been used safely in clinical trials via hepatic arterial infusion in patients with unresectable liver metastases (NCT02316028), which is promising in the context of high risk UM patients [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…While large-scale epigenetic changes have been documented in UM tumors, and these changes have been significantly related to prognosis, there are currently no approved treatments using these agents in UM. In vitro, treatment with epigenetic modifying drugs has been shown to reduce growth and invasiveness in UM cell lines, and decitabine (a DNMT inhibitor) in combination with MEK inhibition has been shown to suppress growth in UM cells [ 39 , 40 ]. Additionally, decitabine has been used safely in clinical trials via hepatic arterial infusion in patients with unresectable liver metastases (NCT02316028), which is promising in the context of high risk UM patients [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The demethylating agent 5‐Aza—also in combination with radiation—has been shown to decrease growth and invasion in uveal (OCM1, OCM3, 92.1) and cutaneous melanoma cell cultures. In a murine cutaneous melanoma intraocular xenograft model, the number of lung metastases was reduced if the cells were exposed to 5‐Aza prior to subretinal injection . The same study also reported a subsequent decrease in LINE‐1 methylation in cell cultures after 5‐Aza treatment.…”
Section: Epigenetic Treatment Approachesmentioning
confidence: 78%
“…In a murine cutaneous melanoma intraocular xenograft model, the number of lung metastases was reduced if the cells were exposed to 5-Aza prior to subretinal injection. 118 The same study also reported a subsequent decrease in LINE-1 methylation in cell cultures after 5-Aza treatment.…”
Section: Epigenetic Treatment Approachesmentioning
confidence: 80%
“…Epigenetic drugs, including DNA methyltransferase (DNMT) inhibitors and HDAC inhibitors, have been shown to have anticancer properties and are beginning to be investigated for ocular tumors with hopes of restoring normal control of neoplastic genomes 42,43. Vidaza (5-azacytidine), a DNMT inhibitor, has been shown to reduce ocular metastasis to the lung in murine xenograft models 42,44. Tenovin-6, which inhibits the class 3 HDAC sirtuin 1 and 2, has shown promise in eliminating UM tumor cells and cancer stem cells 45…”
Section: Discussionmentioning
confidence: 99%